A neurodegeneration checkpoint mediated by REST protects against the onset of Alzheimer’s disease - Aron, Liviu; Qiu, Chenxi; Ngian, Zhen Kai; Liang, Marianna; Drake, Derek; Choi, Jaejoon; Fernandez, Marty A.; Roche, Perle; Bunting, Emma L.; Lacey, Ella K.; Hamplova, Sara E.; Yuan, Monlan; et al. (Nature communications, 2023)
Many aging individuals accumulate the pathology of Alzheimer’s disease (AD) without evidence of cognitive decline. Here we describe an integrated neurodegeneration checkpoint response to early pathological changes that restricts further disease progression and preserves cognitive function. Checkpoint activation is mediated by the REST transcriptional repressor, which is induced in cognitively-intact aging humans and AD mouse models at the onset of amyloid β-protein (Aβ) deposition and tau accumulation. REST induction is mediated by the unfolded protein response together with β-catenin signaling. A consequence of this response is the targeting of REST to genes involved in key pathogenic pathways, resulting in downregulation of gamma secretase, tau kinases, and pro-apoptotic proteins. Deletion of REST in the 3xTg and J20 AD mouse models accelerates Aβ deposition and the accumulation of misfolded and phosphorylated tau, leading to neurodegeneration and cognitive decline. Conversely, viral-mediated overexpression of REST in the hippocampus suppresses Aβ and tau pathology. Thus, REST mediates a neurodegeneration checkpoint response with multiple molecular targets that may protect against the onset of AD. The mechanisms that underlie cognitive resilience during aging are poorly understood. Here, the authors describe a neurodegeneration checkpoint response mediated by the transcription factor REST that protects against the onset of Alzheimer’s disease.